Seed Packets: An Economic Opportunity for Native Wildflower Seed Producers - Jeffrey G. Norcini; Linda B. Landrum; George L. Harrison; Terry Zinn (EDIS, 2007)
ENH-1049, a 5-page illustrated fact sheet by Jeffrey G. Norcini, Linda B. Landrum, George L. Harrison, and Terry Zinn, provides information for growers selling or planning to sell native wildflower seed packets. Includes sections on seed production/harvest, labeling and packaging, costs and marketing, and resources. Published by the UF Department of Environmental Horticulture, December 2006.